A role for gene-environment interactions in Autism Spectrum Disorder is suggested by an excess of potentially pathogenic variants in genes regulating exposure to toxicants - Santos, J.X. (2018)
Objective: Identify potentially pathogenic CNVs and SNVs targeting genes involved in regulation of toxins exposure, namely in detoxification processes and physiological permeability barriers (blood-brain barrier and placenta), in individuals with ASD.